2011
DOI: 10.1145/1978542.1978561
|View full text |Cite
|
Sign up to set email alerts
|

Gender and computing conference papers

Abstract: 72 CommuniCations of th e aC m | au g uST 2 0 1 1 | vo l . 5 4 | n o. 8 contributed articlesIllustratIoN by NaNet te hoo gsl ag sch Olars Kn Ow t h at diversity of thought produces better and faster solutions to complex problems. 20 For this reason, as well as other practical and ethical reasons, the computing disciplines strive to improve women's representation in the field. 5 These efforts often concentrate on piquing the interest of young girls and college students but less often on women's engagement as le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 14 publications
(10 reference statements)
1
25
4
Order By: Relevance
“…Articles about authorship in software engineering are not common, with some exceptions like Ren and Taylor (2007) or the annual publication-based assessment of scholars and institutions that is published in the Journal of Systems and Software (JSS) since 1994 (Wong et al 2011). Some of the results of this study differ with respect to the ones reported, for example, by Cohoon et al (2011) that indicate a small increase in the number of articles published by lone authors at ACM-sponsored conferences for the computing domain. They also report that by 2008, 97 % of all conference articles have 2 or more authors, which substantially differs from our results (87.1 %).…”
Section: Discussioncontrasting
confidence: 61%
“…Articles about authorship in software engineering are not common, with some exceptions like Ren and Taylor (2007) or the annual publication-based assessment of scholars and institutions that is published in the Journal of Systems and Software (JSS) since 1994 (Wong et al 2011). Some of the results of this study differ with respect to the ones reported, for example, by Cohoon et al (2011) that indicate a small increase in the number of articles published by lone authors at ACM-sponsored conferences for the computing domain. They also report that by 2008, 97 % of all conference articles have 2 or more authors, which substantially differs from our results (87.1 %).…”
Section: Discussioncontrasting
confidence: 61%
“…Previous recent work by Cavero et al (2014) and Fernandes (2014) has shown that the number of authors per scientific articles is increasing, whenever data for CS in general or software engineering in particular are analysed. In the present article, we extend previous studies on authorship trends (e.g., Gu 2002;Greene 2007;Cohoon et al 2011;Wainer et al 2013;Cavero et al 2014;Fernandes 2014;Garousi and Fernandes 2016) to a significant number of areas within CS, on the basis of a sample of almost 190,000 curated references. As explained in detail in the next section, the sample used in this work follows the framework described by Wainer et al (2013).…”
Section: Introductionsupporting
confidence: 55%
“…Fewer women are taking CS at the college level [16], [17], which is also reflected by the lower number of female authors on CS conference publications, and the lower number of female role models. There is recent evidence, however, that the number may be rising [18].…”
Section: Under-representation Of Women In Cs and Confidence Gapmentioning
confidence: 99%